The Academic Self-Efficacy Among Undergraduates: The Role of Gender, CGPA and Trait Emotional Intelligence - Iffah Adlina, Ibrahim; Tan, Kock Wah (UNIMAS, 2020)
Academic self-efficacy is important for students which will help them to perform better in studies. This study aims to explore the level of academic self-efficacy among UNIMAS undergraduates based on gender, CGPA and trait emotional intelligence. The samples ofstudy involved are 50 male and 50 female participants which consists of final year students from Faculty of Cognitive Sciences and Human Development. The academic self-efficacy of the students is measured using the questionnaire adopted from a study by Sachitra and Bandara (2017) and The Short Form (TEIQue-SF) Trait Emotional Intelligence Questionnaire is used to measure the trait emotional intelligence of the undergraduates. The result was analyzed using descriptive analysis and inferential analysis; independent samples t-test, One-Way ANOVA and Pearson’s correlation. The results of the study have shown that female students have higher academic self-efficacy compared to male students. In addition, students who obtain a higher CGPA also have higher self-efficacy. There was also a small positive correlation between trait emotional intelligence and academic self-efficacy.